Using Experimental Evidence to Inform Firm Support Programs in Developing Countries - Grover, Arti; Imbruno, Michele (World Bank, Washington, DC, 2020)
Countries design programs for supporting firms, with varying levels of success. Firm growth is constrained by several factors, such as low firm capabilities (e.g. management), availability of finance, and access to markets. Based on the available experimental evidence on firm support programs in developing countries, this paper makes three broad observations. First, there are huge knowledge gaps in understanding the success of instruments that alleviate firm constraints. Various instruments, such as early-stage equity finance, incubators, and accelerators, remain untested due to the lack of good design, results framework, or monitoring and evaluation systems and so on. Second, since these interventions are expensive, policy makers expect such programs to be designed more effectively to pursue their objectives. However, evidence provides little guidance on the criterion for firm selection because the existing evaluations of instruments reveal little information on the heterogeneous impact by firm characteristics, such as the age, size, sector, and location of firms. Third, most interventions seek to address only one of the broad constraints faced by firms. To this end, the paper concludes with a novel proposal for a firm support program that attempts to sequentially address multiple constraints to firm growth. This program will be implemented in Malawi through the "Financial Inclusion and Entrepreneurship Scaling" project.